A clinical trial of the prolactin inhibitor Metergoline in the treatment of canine pseudopregnancy - Castex, Gervasio; Corrada, Yanina; Gobello, Cristina (Revista Científica de la Facultad de Ciencias Veterinarias, 2010)
Canine pseudopregnancy is a syndrome, characterized by signs such as nesting, weight gain, mammary enlargement and lactation, which appear in nonpregnant bitches 6 to 12 weeks after estrus. The intensity of these signs is extremely variable among bitches. Metergoline is essentially a serotoninergic antagonist that inhibits prolactin secretion. A total of 24 cross and pure-bred, overtly pseudopregnant bitches, were randomly allocated to two groups of 10 and 14 animals respectively each: placebo (PL) and metergoline (ME, treated with metergoline 0.1 mg/kg q12h PO for 10 days). On days -1, 7 and 14 (day 0: beginning of the treatment) all the animals were classified into grades of intensity of pseudopregnancy clinical signs (II, I, 0). Presence or absence of treatment side effects were also recorded. On day 7 of the protocol, 5/14 and 3/10 of the bitches of the ME and PL groups, respectively achieved grade I , while 8/14 and 0/10 of the same groups achieved grade 0 (P 0.03). On day 14, 3/14 and 5/10 of the bitches of the ME and PL groups, respectively achieved grade I, while ?10/14 and 0/10 of the same groups achieved grade 0 (P 0.01). Side effects were mild and did not lead to termination of therapy in any case. On day 7, they appeared in 1/14 and 0/10 of the animals of the ME and PL groups, respectively (P 0.01). It was concluded that Metergoline proved to be an efficient and safe drug in the treatment of pseudopregnancy in this group of bitches.